Effect of Disinfection with Hypochlorous Acid on Compatibility with impression materials of type III dental Stone - Ann A.Nasser , Shorouq M. Abass ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Background: In dentistry, dental stone are utilized to create casts for various dental laboratory procedures. Since it comes into contact with the saliva and blood observed on dental impressions, it is regarded as an origin of contamination. Disinfection of the cast has become crucial to preventing infections. Aim: To determine how type III dental stone’s compatibility with the impression materials will be affected by adding a disinfectant (hypochlorous acid (HOCl)) as a water replacement. Methods: A total of 90 specimens of type III dental stone were prepared and separated into three groups, ten specimens for each test group, including group A (control), group B (incorporation of 60 ppm HOCl), and group C (incorporation of 100 ppm HOCl). There were 30 specimens for each type of impression material, including alginate, addition silicone, and zinc oxide eugenol. The specimens of compatibility with the impression material of type III dental stone were evaluated using an optical microscope (Dino-Lite, Taiwan). Results: The results presented that all specimens passed the compatibility with the impression materials test after adding HOCl, which received a score of I. Conclusion: Since type III gypsum products tested for compatibility with impression materials are unaffected by the addition of a hypochlorous acid disinfection solution, this is encouraging.